2020
DOI: 10.2196/22400
|View full text |Cite
|
Sign up to set email alerts
|

A Racially Unbiased, Machine Learning Approach to Prediction of Mortality: Algorithm Development Study

Abstract: Background Racial disparities in health care are well documented in the United States. As machine learning methods become more common in health care settings, it is important to ensure that these methods do not contribute to racial disparities through biased predictions or differential accuracy across racial groups. Objective The goal of the research was to assess a machine learning algorithm intentionally developed to minimize bias in in-hospital morta… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(44 citation statements)
references
References 35 publications
(18 reference statements)
0
42
0
Order By: Relevance
“…The findings of this study have implications for the relevance of ML algorithms in population health research. Similarly, several studies have confirmed the usefulness of ML for population health research and policy decision making in various areas including child undernutrition (26) , women's height (58) , CVD risks (59) and mortality (60) as well as defining treatment effects in epidemiological studies (61) which highlights how ML is increasingly being applied to predict population health outcomes (62) . These findings may also be useful in bias reduction (60) as ML methods can accurately quantify uncertainty when data are scarce, as can be found in sub-Saharan Africa.…”
Section: Discussionmentioning
confidence: 89%
“…The findings of this study have implications for the relevance of ML algorithms in population health research. Similarly, several studies have confirmed the usefulness of ML for population health research and policy decision making in various areas including child undernutrition (26) , women's height (58) , CVD risks (59) and mortality (60) as well as defining treatment effects in epidemiological studies (61) which highlights how ML is increasingly being applied to predict population health outcomes (62) . These findings may also be useful in bias reduction (60) as ML methods can accurately quantify uncertainty when data are scarce, as can be found in sub-Saharan Africa.…”
Section: Discussionmentioning
confidence: 89%
“…Of the 12 studies, 5 (42%) published code used for analysis, 3 (25%) made model development code available [ 34 , 36 , 39 ], 2 (17%) published bias analysis code [ 33 , 36 ], 1 (8%) published code relevant to debiasing [ 30 ], and 1 (8%) published data selection code [ 33 ]. In addition, 1 (8%) study used publicly available code for analysis [ 31 ], and code was specified as available upon request in 1 (8%) study [ 35 ].…”
Section: Resultsmentioning
confidence: 99%
“…48 ML has also been used to identify when standard scoring systems accentuate racial disparities, and models have been designed with the aim of reducing racial bias in outcome predictions. 49 In addition to bias and computational challenges, ML projects introduce the same challenges of any interdisciplinary research project aiming to inform practice and policy. Developing a practical model requires expertise from healthcare epidemiologists, clinicians, computer scientists, and other professionals.…”
Section: Discussionmentioning
confidence: 99%